Pancreatic cancer masquerading as ischemic enteritis on endoscopy - Enrik John T Aguila; Carlos Paolo D Francisco; Jonard T Co (JGH Open, 2021)
Abstract Pancreatic tumors usually produce painless jaundice. Other associated symptoms may be secondary, from a direct extension of the tumor, resulting in bowel obstruction. It is extremely rare that pancreatic malignancy presents with ischemic enteritis by invasion of the major arteries, and no report has documented it endoscopically. We present a rare case of pancreatic adenocarcinoma masquerading as ischemic enteritis diagnosed on enteroscopy and endoscopic ultrasound. An initial computed tomography (CT) scan performed in another hospital showed long segmental wall thickening involving the third part of the duodenum to the proximal segment of the jejunum. The patient was referred to our institution for enteroscopy, which showed a poorly distensible third part of the duodenum with purplish mucosa starting at the fourth part of the duodenum until the proximal jejunum. With suspicion of ischemic enteritis, a mesenteric CT angiography was performed, which showed a long segment circumferential wall thickening of the duodenum to jejunum with fullness of the pancreatic head and uncinate process that encases the superior mesenteric artery. Endoscopic ultrasound (EUS) showed a hypoechoic lesion at the head of the pancreas. EUS‐guided fine‐needle biopsy was performed, which revealed pancreatic adenocarcinoma on histopathology.